Identifying Ecological Priority Areas for Synergistic Conservation across Scales in the Asian Water Tower Region - Guangjin Zhou; Yizhong Huan; Lingqing Wang; Riqi Zhang; Tao Liang; Matilda Eve Dunn; Fuqi Yao; Yali Tong (Ecosystem Health and Sustainability, 2023)
The region containing 17 Asian countries located on and around the Qinghai-Tibetan Plateau (Asian Water Tower) is experiencing a serious ecological crisis, representing a major challenge for both Asian and global ecological conservation. Identifying and synergizing multiscale ecological conservation priorities for this region can promote progress toward the goals proposed by the post-2020 global biodiversity framework (e.g., protecting 30% of the planet) and Sustainable Development Goal 15 (life on land). We mapped the importance of and interactions among 5 key ecosystem services (ESs) (water conservation, carbon sequestration, sand fixation, soil conservation, and biodiversity conservation) across this region and identified areas where synergistic ESs were present. We further identified synergistic national- and regional-scaled conservation priority areas. The areas with “high importance” of the composite ESs accounted for 18.9% of the total region. Seventy-two percent of this area was found to have an overlap of at least 2 ESs. Approximately 33.3% of the study region was identified as a regional-scaled conservation priority area, which can be implemented synergistically in each country. Approximately 22.5% of the land in the priority area was nonecological land, which can seriously compromise the importance of ESs. A set of actions to support achieving global conservation goals, such as strengthening the control of anthropogenic activities in priority conservation areas, providing additional efforts and assistance to some key countries, and developing effective ecological compensation schemes, was provided.